Layered perovskite GdBa0·5Sr0·5CoCuO5+δ as cathode material for intermediate-temperature solid oxide fuel cells. (July 2014) - Wang, B.; Long, G.; Ji, Y.; Pang, M.; Meng, X.
<x content-type="archive" xml:space="preserve">Abstract</x> Layered GdBa0·5Sr0·5CoCuO5+δ(GBSCCu) perovskite oxide is synthesised using an ethylenediaminetetraacetic acid (EDTA)–citrate combined method. Electrochemical performances are investigated as a novel cathode material for intermediate-temperature solid oxide fuel cells. The cathode GBSCCu chemical compatibility with Gd0·1Ce0·9O1·95 (GDC) electrolyte is examined below 950°C. The electrical conductivity value of the GBSCCu sample reaches a maximum of 147 Scm−1 at 750°C in air. The thermal expansion coefficient of the GBSCCu sample is 16·9×10−6 K−1 between 30°C and 900°C. The polarisation resistance of GBSCCu on the GDC electrolyte is 0·102 Ω cm2 at 800°C. The maximum power density of a single cell with a GBSCCu–GDC composite cathode on the 300 μm thick GDC electrolyte reaches 402 mW cm−2. These results indicate that GBSCCu is a potential cathode material for GDC electrolyte intermediate-temperaturte solid oxide fuel cells(IT-SOFCs).